Silica sulfuric acid: a reusable solid catalyst for one pot synthesis of densely substituted pyrrole-fused isocoumarins under solvent-free conditions - Pathak, Sudipta; Debnath, Kamalesh; Pramanik, Animesh (Beilstein Journal of Organic Chemistry, 2013)
A convenient and efficient methodology for the synthesis of densely substituted pyrrole-fused isocoumarins, which employs solid-supported silica sulfuric acid (SSA) as catalyst, has been developed. When the mixture of ninhydrin adducts of acetylacetone/ethyl acetoacetate and primary amines was heated on the solid surface of SSA under solvent-free conditions, the pyrrole-fused isocoumarins were formed in good yields. This synthetic method has several advantages such as the employment of solvent-free reaction conditions without the use of any toxic reagents and metal catalysts, the ease of product isolation, the use of a recyclable catalyst, the low cost, the easy availability of the starting materials, and the excellent yields of products.
Keywords: green chemistry; pyrrole-fused isocoumarin; reusable solid support; silica sulfuric acid; solvent-free condition